Analisis Peran Pendidik Akidah Akhlak terhadap Motivasi Peserta Didik di MTs Sulamul Huda Ponorogo - Yusda Herdian Syahrul Fuad (Muaddib: Jurnal Pendidikan Agama Islam, 2024)
The success of a lesson cannot be separated from the teacher's role as an educator in the madrasah environment. In the learning process, teachers are required to be able to have the ability to motivate their students so as to create a conducive and enjoyable atmosphere in the learning process. In conveying the material the teacher is expected to be able to provide motivation to students, so that students are proud of what they learn. The role of educators or teachers to help increase learning motivation is very large. The research focus in this study is what is the role of Akidah Akhlak educators in motivating and increasing the learning motivation of class IX students at MTs Sulamul Huda Ponorogo and what obstacles are often faced by Akidah Akhlak educators when increasing the learning motivation of class IX students at MTs Sulamul Huda Ponorogo. This type of research is descriptive qualitative research. Determination of the subject using purposive sampling. In collecting data, researchers used interviews, observation, documentation and literature studies. Methods of data analysis using data presentation, data reduction, and drawing conclusions. Data validity uses source triangulation. This study draws the following conclusions: The role of akidah moral educators as motivators in increasing students' motivation to study at MTs Sulamul Huda Ponorogo is shown by the presence of teachers as motivators, directors and facilitators. Teachers must set a good example, encourage student learning motivation, create a fun learning atmosphere, develop students' abilities. The obstacles faced by the teacher in learning the Akidah Akhlak are obstacles from internal student factors such as: the interest of students and the level of understanding. Meanwhile, student external factors, namely the influence of student association, a conducive environment and a harmonious family.